Topical ophthalmic administration: Can a drug instilled onto the ocular surface exert an effect at the back of the eye? - del Amo, Eva M. (Frontiers in Drug Delivery, 2022)
Topical ophthalmic instillation is an appealing strategy to deliver drugs to the back of the eye to treat retinal diseases such as neovascular age-related macular degeneration, diabetic retinopathy, retinal vein occlusion, and glaucomatous optic neuropathy. It has several advantages such as being non-invasive and user-friendly, e.g., allowing self-administration. However, the main obstacle has been how to achieve therapeutic drug concentrations in the retina due to the eye’s protective mechanisms, flows, and barriers. Less than 4% of the instilled drug dose enters the anterior chamber, and much less is expected to reach the posterior segment. It is crucial to understand a drug’s topical pharmacokinetics in humans and how one can extrapolate data from rabbits to humans. In this review, the available data on the retina and vitreous drug concentrations from pharmacokinetics studies conducted in human patients and rabbits have been compiled, together with the critical physiological factors to be considered for this route of administration. Improvements in the design of preclinical studies are suggested to increase their translatability to the treatment of human patients. Finally, the current status of clinical trials with topical ophthalmic formulations intended to treat the back of the eye is depicted. At present, no topical ophthalmic formulations to treat neovascular age-related macular degeneration or other retinal neurodegenerative illnesses have reached the market.